Digital Entrepreneurial Mindset Development: Strategies to Increase the Economic Competitiveness of Indonesia's Gen Z in the E-Commerce Era: a Study Systematic Literature Review - Ilma Wulansari Hasdiansa (Economics and Business Journal (ECBIS), 2025)
This systematic literature review (SLR) article discusses the role of e-commerce education to increase the economic growth of generation z (Gen Z) in Indonesia. The purpose of this study is to determine aspects of e-commerce education to support the economic growth of Gen Z in Indonesia. E-commerce education is understood as a place to form the right self-potential to improve Gen Z's digital skills. The method of writing a systematic literature review (SLR) article is a library research method sourced from the Scopus database. The results of this literature review study found that e-commerce education integrated with industry can create Gen Z who have skills in managing digital technology, creativity, and are able to adapt according to the job market. The implications of this study are to encourage the government, academics, and industry players to assist Gen Z through e-commerce education so that their potential becomes a source of economic growth in Indonesia in the future.